The Social Perception of Political Corruption vs the Evaluation of Honesty of Political Authorities - Wojtasik, Waldemar (Political Preferences, 2017)
Political corruption is a multidimensional phenomenon, concerning political authorities at all possible levels. It is defined as the abuse of power by political entities in order to obtain personal benefits in the form of greater power or wealth. It shows that the subject of political corruption is not only material benefits but also the mechanisms of increasing the influence or special treatment. The character of political corruption results in the public interest in it, enhanced by the public character of the individuals it refers to. It is also influenced by the processual character of the phenomenon itself, but first of all by the specific attractive nature of corruption in social awareness. The article presents the findings of research concerning opinions on political corruption. Its goal is to study the relationships between the respondents' opinions on political authorities' honesty and the determinants of corrupt phenomena. The main research question is: Is there any relationship between the person's opinion on political authorities' honesty and the person's perception of political corruption? The hypothesis related to the question assumes there is a connection between the perception of political authorities' honesty and the evaluation of components of political corruption. The research is part of a research project carried out by the IPSO ORDO Academic Foundation on the perception of the corruption phenomenon in the public domain. Key words: corruption, political corruption, political power, honesty